2020
DOI: 10.1186/s13006-020-00342-4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of workplace breastfeeding in a provincial government setting: a qualitative exploratory study among managers and mothers in South Africa

Abstract: Background Return to employment is a major barrier to breastfeeding continuation, globally and in the Southern African context. The Lancet Breastfeeding Series revealed an explicit need for research exploring breastfeeding as a workplace issue in low- and middle-income countries. A dearth of research on workplace breastfeeding in South Africa calls for attention to this topic. This study sought to explore breastfeeding at work experiences from the perspective of employed mothers and senior mana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…In Kenya, Ethiopia, and South Africa, studies reported that the lack of a specific location to express or store breastmilk at workplaces was a barrier to EBF [ 64 , 84 ]. In Tanzania and South Africa, mothers were denied breastfeeding breaks during working hours, which affected EBF [ 65 , 81 , 94 , 95 ]. Other studies reported that mothers felt stressed while working, as they did not find time to eat or worked for long hours, which affected their ability to breastfeed [ 66 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, Ethiopia, and South Africa, studies reported that the lack of a specific location to express or store breastmilk at workplaces was a barrier to EBF [ 64 , 84 ]. In Tanzania and South Africa, mothers were denied breastfeeding breaks during working hours, which affected EBF [ 65 , 81 , 94 , 95 ]. Other studies reported that mothers felt stressed while working, as they did not find time to eat or worked for long hours, which affected their ability to breastfeed [ 66 , 80 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Este aspecto está em consonância com a literatura, que aponta o apoio no local de trabalho como aspecto crucial e positivo na duração da amamentação 15 . O ato do chefe encorajar verbalmente esse desejo vem demonstrando ser contributivo, gera o comprometimento, melhora a produtividade e diminui o absenteísmo e a insatisfação com o trabalho [14][15][16][17] , se tornando ainda mais relevante durante o período inicial após o retorno ao trabalho, considerado como momento crítico para a continuidade para amamentação 18 .…”
Section: Discussionunclassified
“…Uma sala de amamentação adequada, privada, com insumos para a ordenha das mamas é crucial e, além de contribuir significativamente para a continuidade da amamentação, possui baixo custo de implementação e manutenção para a organização 17,18 , o que novamente reforça a importância da construção desses ambientes de lactação, conforme destacado pelas participantes da presente pesquisa.…”
Section: Discussionunclassified
“…This is legislated in the labor laws of some countries, for instance the South African employment act legislates for breastfeeding/milk expression breaks for lactating mothers 26 . However, a major challenge is that many employers and employees are not aware of these policies or their rights 27 . In addition, although these suggested policies are very good, the lack of proper implementation, monitoring and tracking prevent success.…”
Section: The Role Of Institutions In Improving Gender Equity In Sciencementioning
confidence: 99%